Interior Design of Basketball Center in Surakarta with Pop Art Theme - Marinda Humarahma; IF.Bambang Sulistyono (Pendhapa, 2021)
Basketball Center Interior Design in Surakarta with Pop Art Theme aims to (1) Create an interior design of sports hall that is able to attract the attention of the public in exercising and maintaining health. (2) Create a basketball centre that can increase the passion for exercising while practising or competing through the atmosphere. The methods used in this study are programming that includes library studies, surveys, interviews. Then data analysis, idea development, and design methods. From this analysis can be summed up several things: (1) Basketball centre interior design as a physical fitness centre and a container of sports activities especially basketball sports designed to influence the psychology of players. (2) Shapes, colours and materials applied according to the theme namely pop art on all interior elements. (3) The atmosphere of the room that is raised is a cosy, cheerful, unique, interesting, free, and limitless atmosphere